Estudo do tempo mínimo de maturação para segurança do queijo Minas artesanal da Serra Geral - Roberta Ribeiro da Cruz Cangussu (2018)
The State of Minas Gerais is known for the production of artisanal cheeses made from raw milk, however the commercialization of these cheeses manufactured in the northern cities of the State still occurs in the informality. Thus, it was aimed to characterize and determine the minimum ripening time to reach the legal parameters of the artisanal cheeses of the Serra Geral region, located in the state of Minas Gerais. Eight samples from four producers were acquired, totaling 32 samples of artisanal cheeses. The cheeses were matured at room temperature between 25 and 30 ° C and under refrigeration. The physical characteristics, texture profile and microbiological quality were determined with seven, 15, 30 and 60 maturation days. The ripening at room temperature proved to be more efficient in reducing microbiological contamination. Cheeses with 15 days of ripening at room temperature presented the parameters of Coliforms at 35 ° C and Escherichia coli according to legal determination. However, at the same time, they had an average count of 4.48 Log UFC.mL-1 for Staphylococcus aureus, higher than the current legislation, making it safe only with 60 days. They were not detected in 25 g of the Listeria sp. and Salmonella sp. During ripening, the weight, height and diameter of the samples decreased. All six texture parameters changed during the course of ripening and presented differences when evaluated at room temperature and under refrigeration.